Effects of Prenatal Exposure to Inflammation Coupled With Stress Exposure During Adolescence on Cognition and Synaptic Protein Levels in Aged CD-1 Mice - Zhang, Zhe-Zhe; Zhuang, Zhan-Qiang; Sun, Shi-Yu; Ge, He-Hua; Wu, Yong-Fang; Cao, Lei; Xia, Lan; Yang, Qi-Gang; Wang, Fang; Chen, Gui-Hai (Frontiers in Aging Neuroscience, 2020)
Age-associated impairment of spatial learning and memory (AISLM) presents substantial challenges to our health and society. Increasing evidence has indicated that embryonic exposure to inflammation accelerates the AISLM, and this can be attributable, at least partly, to changed synaptic plasticity associated with the activities of various proteins. However, it is still uncertain whether social psychological factors affect this AISLM and/or the expression of synaptic protein-associated genes. Synaptotagmin-1 (Syt1) and activity-regulated cytoskeleton-associated protein (Arc) are two synaptic proteins closely related to cognitive functions. In this study, pregnant CD-1 mice received daily intraperitoneal injections of lipopolysaccharide (LPS) (50 μg/kg) or normal saline at days 15–17 of gestation, and half of the offspring of each group were then subjected to stress for 28 days in adolescence. The Morris water maze (MWM) test was used to separately evaluate spatial learning and memory at 3 and 15 months of age, while western blotting and RNAscope assays were used to measure the protein and mRNA levels of Arc and Syt1 in the hippocampus. The results showed that, at 15 months of age, control mice had worse cognitive ability and higher protein and mRNA levels of Arc and Syt1 than their younger counterparts. Embryonic exposure to inflammation or exposure to stress in adolescence aggravated the AISLM, as well as the age-related increase in Arc and Syt1 expression. Moreover, the hippocampal protein and mRNA levels of Arc and Syt1 were significantly correlated with the performance in the learning and memory periods of the MWM test, especially in the mice that had suffered adverse insults in early life. Our findings indicated that prenatal exposure to inflammation or stress exposure in adolescence exacerbated the AISLM and age-related upregulation of Arc and Syt1 expression, and these effects were linked to cognitive impairments in CD-1 mice exposed to adverse factors in early life.